Proof of endorment Algérien législation - الهمال الشيخ; بحماوي الشريف (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2023)
In light of the policy of the Algerian state based on the orientation of investments and the abandonment of oil rents, the endowment has emerged as an important investment resource and a fertile field for competition to do good, so the Algerian state has given it its attention and made it a priority of its legislative policies through the laws it issued, which aims to protect the endowment from various forms of infringement One of the most prominent forms of protection is the organization of the means of establishing endowment in accordance with the principle of freedom of proof enshrined in Article 35 of the Endowment Law 10/91, which states that the endowment is established by all legitimate and legal methods the study aims to show the most important means adopted by the Algerian legislator in proving the legal endowments, including legitimacy, and the study concluded that subjecting the endowment to the general rules of proof is unavoidable, taking into account the specificity of righteousness and goodness that distinguishes it.